High-Intensity Interval Training Minimizes the Deleterious Effects of Arterial Hypertension on the Urinary Bladder of Spontaneously Hypertensive Rats - Batista, Victor Rogério Garcia [UNESP]; Correia, Rafael Ribeiro [UNESP]; Fernandes, Vítor S.; Veras, Allice Santos Cruz [UNESP]; Tavares, Maria Eduarda Almeida [UNESP]; Chaves-Neto, Antonio Hernandes [UNESP]; Fiais, Gabriela Alice [UNESP]; De Souza, Francilene Lima Agostinho [UNESP]; Pacagnelli, Francis Lopes; Suggett, Cara Beth; Teixeira, Giovana Rampazzo [UNESP] (Hindawi, 2023)
Arterial hypertension promotes urological complications by modifying the functional capacity of the urinary bladder. On the other hand, physical exercise has been suggested as a nonpharmacological tool to improve blood pressure regulation. High-intensity interval training (HIIT) can effectively increase peak oxygen consumption, body composition, physical fitness, and health-related characteristics of adults; however, its action on the urinary bladder is little discussed. In the present study, we verified the effect of HIIT on the modulation of the redox state, morphology, and inflammatory and apoptotic processes of the urinary bladder of hypertensive rats. Spontaneously hypertensive rats (SHR) were divided into two groups: SHR sedentary and SHR submitted to HIIT. Arterial hypertension promoted an increase in the plasma redox state, modified the volume of the urinary bladder, and increased collagen deposition in detrusor muscle. It was also possible to identify, in the sedentary SHR group, an increase in inflammatory markers such as IL-6 and TNF-α in the urinary bladder, as well as a reduction in BAX expression. However, in the HIIT group, reduced blood pressure levels were observed, together with an improvement in morphology, such as a decrease in collagen deposition. HIIT also regulated the proinflammatory response, promoting increases in IL-10 and BAX expressions and in the number of plasma antioxidant enzymes. The present work highlights the intracellular pathways involved with the oxidative and inflammatory capacity of the urinary bladder and the potential effect of HIIT on the regulation of the urothelium and detrusor muscle of hypertensive rats.